Effectiveness and Cardiac Safety of Bedaquiline-Based Therapy for Drug-Resistant Tuberculosis: A Prospective Cohort Study. (21st April 2021) - Brust, James C M; Gandhi, Neel R; Wasserman, Sean; Maartens, Gary; Omar, Shaheed V; Ismail, Nazir A; Campbell, Angela; Joseph, Lindsay; Hahn, Alexandria; Allana, Salim; Hernandez-Romieu, Alfonso C; Zhang, Chenshu; et al.
Abstract: Background: Bedaquiline improves treatment outcomes in patients with rifampin-resistant (RR) tuberculosis but prolongs the QT interval and carries a black-box warning from the US Food and Drug Administration. The World Health Organization recommends that all patients with RR tuberculosis receive a regimen containing bedaquiline, yet a phase 3 clinical trial demonstrating its cardiac safety has not been published. Methods: We conducted an observational cohort study of patients with RR tuberculosis from 3 provinces in South Africa who received regimens containing bedaquiline. We performed rigorous cardiac monitoring, which included obtaining electrocardiograms in triplicate at 4 time points during bedaquiline therapy. Participants were followed up until the end of therapy or 24 months. Outcomes included final tuberculosis treatment outcome and QT interval prolongation (QT prolongation), defined as any QT interval corrected by the Fridericia method (QTcF) >500 ms or an absolute change from baseline (ΔQTcF) >60 ms. Results: We enrolled 195 eligible participants, of whom 40% had extensively drug-resistant tuberculosis. Most participants (97%) received concurrent clofazimine. Of the participants, 74% were cured or successfully completed treatment, and outcomes did not differ by human immunodeficiency virus status. QTcF continued to increase throughout bedaquiline therapy, with a mean increase (standard deviation) of 23.7 (22.7) ms from baseline to month 6. Four participants experienced a QTcF >500 ms and 19 experienced a ΔQTcF >60 ms. Older age was independently associated with QT prolongation. QT prolongation was neither more common nor more severe in participants receiving concurrent lopinavir-ritonavir. Conclusions: Severe QT prolongation was uncommon and did not require permanent discontinuation of either bedaquiline or clofazimine. Close monitoring of the QT interval may be advisable in older patients. Abstract : Severe prolongation of the QT interval corrected by the Fridericia method (QTcF) was uncommon among participants treated for multidrug-resistant or extensively drug-resistant tuberculosis with a regimen containing both bedaquiline and clofazimine. Outcomes were favorable in this setting with high human immunodeficiency virus prevalence. Participants receiving concurrent lopinavir-ritonavir did not experience further QTcF prolongation.